№182
Рейтинг: 0.0 з 5 (0 голос.)

1) x4 = 16, x4 = 24 або x4 = (–2)4, x = –2, x = 2.
Відповідь: –2 і 2.

2) x5 = –243, x5 = (–3)5, x = –3.
Відповідь: –3.

3) x2 + x = 2, x(x + 1) = 2, x = 1 або x = –2.
Відповідь: 1 і –2.

4) x3 + x2 = 6x, x3 + x2 – 6x = 0, x(x2 + x – 6) = 0.
Спростимо вираз x2 + x – 6:
x2 + x – 6 = x2– 9 + x + 3 = (x – 3)(x + 3) + (x + 3) = (x + 3)(x – 3 + 1) = (x + 3)(x – 2),
тоді отримаємо x(x + 3)(x – 2) = 0, отже x = 0 або x = –3 і x = 2.
Відповідь: –3, 0 і 2.

Відгуки

Всього коментарів: 0
avatar

Відгуки

avatar
up